2018
DOI: 10.1097/mph.0000000000001220
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine-associated Neuropathy With Antifungal Usage: A Kaiser Northern California Experience

Abstract: The dose-limiting toxicity for vincristine is peripheral neuropathy which can be potentiated with concurrent usage of azole antifungals. The current retrospective study assessed the incidence of concurrent vincristine and azole antifungal usage to determine if it led to increased neurotoxicity for the Kaiser Northern California pediatric acute lymphoblastic leukemia (ALL) and Hodgkin lymphoma patient population. Data were obtained from the electronic medical record (2007 to 2014). In total, 130 subjects receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Thus, coadministration of vincristine and itraconazole decreases the metabolism of vincristine to a greater extent than coadministration with fluconazole, causing notably enhanced neurotoxicity. Consistently, three studies did not observe significant differences in neuropathy upon fluconazole treatment [69, 71, 73], whereas six independent studies report higher incidence and severe neuropathy upon itraconazole treatment [1, 70, 72, 7476] (Table 3).…”
Section: Resultsmentioning
confidence: 63%
“…Thus, coadministration of vincristine and itraconazole decreases the metabolism of vincristine to a greater extent than coadministration with fluconazole, causing notably enhanced neurotoxicity. Consistently, three studies did not observe significant differences in neuropathy upon fluconazole treatment [69, 71, 73], whereas six independent studies report higher incidence and severe neuropathy upon itraconazole treatment [1, 70, 72, 7476] (Table 3).…”
Section: Resultsmentioning
confidence: 63%
“…It has been previously reported that azole antifungal treatment concurrent with VCR dosing influences the development of VIPN [ 22 , 23 , 24 ]. However, our study does not show any relationship between VCR PK and azole treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a drug–drug interaction between VCR and concurrent treatment with many azole antifungals was previously reported [ 22 , 23 , 24 ]. These azole antifungals are frequently used during intensive chemotherapeutic treatment in children for the prevention or treatment of invasive fungal infections [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…As said before, vincristine is metabolized by CYP3A4 in the liver. In pediatric patients, it is frequently described as the association between VIPN and concomitant interacting treatments with CYP3A4 inhibitors [ 59 ]. The azole antifungals are strong CYP3A4 inhibitors and neurotoxic themselves, even in the absence of other neurotoxic chemotherapy; consequently they should be avoided during vincristine regimens [ 60 , 61 ].…”
Section: Treatment-related Risk Factors For Vipnmentioning
confidence: 99%